Ética del escritor para un mundo de la postverdad - gil claros, mario germán (2020)
This article focuses its reflection on the ethics of the writer for our contemporary world, today crossed by post-truth in mass writing, addressed to what is still called public opinion. For this, Kierkegaard and other thinkers help us understand what would be an ethic of the writer for our present.